2022
DOI: 10.3389/fphar.2021.756997
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation Attenuates Acute Skeletal Muscle Injury Induced by Hepatic Ischemia/Reperfusion Injury in Rats

Abstract: Vagus nerve stimulation (VNS) has a protective effect on distal organ injury after ischemia/reperfusion (I/R) injury. We aimed to investigate the protective efficacy of VNS on hepatic I/R injury-induced acute skeletal muscle injury and explore its underlying mechanisms. To test this hypothesis, male Sprague-Dawley rats were randomly divided into three groups: sham group (sham operation, n = 6); I/R group (hepatic I/R with sham VNS, n = 6); and VNS group (hepatic I/R with VNS, n = 6). A hepatic I/R injury model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Furthermore, proteomic analysis revealed that plasma glutathione and glutathione peroxidase levels were significantly increased by VNS, implying that the protective effect may be related to glutathione metabolism. Furthermore, VNS can also protect distal organs against hepatic IR-induced injury, such as the lung, kidney and skeletal muscle [ [155] , [156] , [157] ]. Currently, there are no clinical trials examining the effect of VNS on hepatic IRI patients, and further studies are needed to confirm its effectiveness.…”
Section: Vns Plays a Protective Role In Iri Of Different Organsmentioning
confidence: 99%
“…Furthermore, proteomic analysis revealed that plasma glutathione and glutathione peroxidase levels were significantly increased by VNS, implying that the protective effect may be related to glutathione metabolism. Furthermore, VNS can also protect distal organs against hepatic IR-induced injury, such as the lung, kidney and skeletal muscle [ [155] , [156] , [157] ]. Currently, there are no clinical trials examining the effect of VNS on hepatic IRI patients, and further studies are needed to confirm its effectiveness.…”
Section: Vns Plays a Protective Role In Iri Of Different Organsmentioning
confidence: 99%
“…Oxidative stress is a pathological process that results from an imbalance between the production and accumulation of reactive oxygen species such as superoxide radicals, hydrogen peroxide, hydroxyl radicals, and singlet oxygen in the cells and the ability of the body system to detoxify them 76,77 . Vagus nerve stimulation (VNS) reduces oxidative stress via silent information regulator 1 (SIRT1), which is a histone of deacetylase of nicotinamide adenine dinucleotide (NAD + ) that helps in the regulation of cell proliferation, differentiation, apoptosis, and metabolism 71,78 …”
Section: Putative Role Of Non‐invasive Vagus Nerve Stimulation In Can...mentioning
confidence: 99%
“…In particular, several important mechanisms have been identified: oxidative stress reduction; inhibition of inflammatory response by targeting two inflammation pathways (the hypothalamic-pituitaryadrenal axis (HPA) and the cholinergic anti-inflammatory pathway) and inhibition of sympathetic activity. 48,70,71 See Table 1 for the summary of the potential VNS parameters The stimulation started 24 h prior to the operation and continued till the 4th postoperative day for patients with cancer [72][73][74][75] ; and Figure 1 for the schematic representation of its mechanisms.…”
Section: Putative Role Of Non-invasive Vagus Nerve Stimulation In Can...mentioning
confidence: 99%
“…Additionally, VNS has been proven to reduce I/R injury in multiple organs, including the kidneys, brain, and heart [9][10][11] . Furthermore, an increasing number of researchers are becoming aware of the potential of VNS on remote organ injury after I/R injury [12][13][14] . However, to the best of our knowledge, whether VNS can also reduce remote kidney injury after hepatic I/R injury remains unknown.…”
Section: Capmentioning
confidence: 99%
“…Subsequently, continuous low-frequency stimulation (HFS, 20 Hz, 0.2 ms in duration, square waves) were delivered. VNS was performed during the entire hepatic I/R process 12 . The stimulus intensity should achieve a 10% reduction in the sinus rate and adjust hourly 10,37 .…”
Section: Vagus Nerve Stimulationmentioning
confidence: 99%